Participación Juvenil Y Su Incidencia En El Desarrollo Local En El Cantón Quevedo - Arana Mero, Janina Alexandra (2025)
Research on youth participation in local development in the canton of Quevedo reflects a reality of significant challenges, but also opportunities to enhance their involvement in public management. The objective was to assess how their involvement can foster sustainable and inclusive development through a mixed qualitative-quantitative approach, which included interviews with local representatives and surveys of adolescents and youth. The results show that the lack of accessible information, key skills such as leadership, communication and knowledge about public policies, as well as youth invisibility, are barriers that limit their active participation in decision-making. However, a high percentage of young people (70.2%) recognize the importance of their involvement, which underscores their willingness to contribute if inclusive mechanisms and effective strategies are implemented. The conclusions highlight that current administrative procedures are complex and not adapted to the needs of young people, perpetuating their exclusion. Likewise, it is evident that, although young people have training deficiencies, they also show interest in acquiring skills that empower them as community leaders. This represents an opportunity to transform apathy into meaningful action. It is recommended to design comprehensive training programs in leadership and public policies, simplify administrative processes, and create inclusive participatory spaces. These strategies should be complemented by information campaigns adapted to youth language and youth-led projects. With these actions, youth will be able to assume a leading role, contributing to the sustainable development of the Quevedo canton.